A Stable Energy Acquisition System Based on Magnetic Circuit Coupled Current Transformer for Transmission Line. Issue 4 (May 2019) - Zhang, Pengyu; Meng, Runquan; Ren, Chunguang; Zhang, Ying
Abstract: With the development of smart grids, high-voltage transmission line monitoring devices has become a new research hotspot, but the supply of stable energy for monitoring devices is a difficult point. By utilizing of current transformer (CT) to obtain stable energy from high-voltage transmission lines is one of promising approaches, but the current variation range of the high-voltage transmission line is often too large to be transformed linearly by the traditional electromagnetic CT. According to impedance matching principle, a method to regulate the load impedance of a CT is proposed in order to acquire energy effectively from a transmission line and provide stable output power. The method to regulate the load impedance of a CT can be implemented by controlling a single-phase PWM rectifier. It is proved by experiment that the PWM rectifier can be adjusted to supply a stable 20V output voltage and 9W output power for the DC load.